RIPK3 Suppresses the Progression of Spontaneous Intestinal Tumorigenesis - Zhao, Qun; Guo, Jian; Cheng, Xinran; Liao, Yingying; Bi, Yun; Gong, Yingxia; Zhang, Xudong; Guo, Yang; Wang, Xianhui; Yu, Wei; Jin, Shu; Tan, Yan; et al. (Frontiers in Oncology, 2021)
Receptor-interacting protein 3 (RIPK3), a member of the family of serine/threonine protein kinases, emerged as a critical regulator of necroptosis. Downregulated expression of RIPK3 is correlated with poor prognosis in multiple tumor types. Here, we show that RIPK3 is involved in the progression of spontaneous intestinal tumorigenesis. As a clinical correlate, reduced expression of RIPK3 is positively associated with histological grade, lymphatic metastasis and poor prognosis in CRC patients. RIPK3-deficient (Ripk3-/-) mice exhibit increased tumor formation in Apcmin/+ spontaneous intestinal tumorigenesis. Apcmin/+Ripk3-/- tumors promote hyperactivation of IL-6/STAT3 signaling, which exacerbates proliferation and inhibits apoptosis. Blocking IL-6 signaling suppressed tumor formation and reduced STAT3 activation in Apcmin/+Ripk3-/- mice. Thus, our results reveal that RIPK3 is a tumor suppressor in spontaneous intestinal tumorigenesis, and implicate targeting the IL-6/STAT3 signaling axis as a potential therapeutic strategy for intestinal tumor patients with reduced RIPK3.